Problems and prospects of improving the organization of international rail transport in the Republic of Kazakhstan - Shakirova, G.A.; Amankeldi, A.A.; Lapbaeva, S.Sh.; Omarkulova, M.B.; Andossova, A.R. (BUKETOV BUSINESS REVIEW, 2023)
Object: To establish the essence and role of the organization of international rail transportation, to identify ways to improve it. To achieve the goal, the following tasks were set and solved: the place and role of the transport system in improving international transportation; the study and evaluation of the effectiveness of the organization of international railway transportation in the Republic of Kazakhstan; the analysis of indicators of international transportation in the Republic of Kazakhstan, carried out by CJSC NC “Kazakhstan Temir Zholy”; to determine the main priorities for the development of the transport industry in order to improve transport support in foreign economic activity. Methods: The methodological basis is formed by the main theories of the classics of economics, the work of foreign and domestic scientists and specialists on the problems of organizing international railway transportation in the Republic of Kazakhstan, as well as a systematic analysis of literature, content analysis of documents, interviews with experts, the method of synthetic analysis and comparative analysis. Findings: Kazakhstan’s railway sector development strategy provides for an international railway transport system offering favorable trade conditions. By 2030, this system will be fast, efficient, affordable and easy to use throughout the region. To achieve this goal, the key tasks are the improvement of railway and multimodal infrastructure, commercialization and reform of railway activities. The integration of these three components into a comprehensive package of reforms and commercialization policies is aimed at making rail transport more attractive and increasing its share in the overall transport network. Conclusions: The most important issue for the development of Kazakhstan is the active participation of Kazakhstan in the international ground corridors connecting Europe and Asia. This is due not only to the effective delivery of products to international markets, but also to the fact that payments from transit transportation fall in favor of the country. Transport infrastructure is a system that is at the root of the industrial economy and society. There is no developed country without high-quality modern highways. Railway transport is the most important means of communication in the transport complex of the Republic, the main link in the transport infrastructure. Due to the geographical position of Kazakhstan, its vast territory, the raw material structure of production, the location of productive forces, the insufficient development of road infrastructure, the role of railway transport in the country’s economy is especially important.